Myxofibrosarcoma of the mandible: a case report and review of the literature - Zhengqiang Li; Xianwen Liu; Quanyin Zhang; Jie Zhang; Mingyi Huang; Shuguang Liu (BMC Oral Health, 2020)
Abstract Background Myxofibrosarcoma (MFS) is a soft tissue sarcoma that commonly occurs in late adult life. It is mainly located in the subcutaneous soft tissues of extremities characterized by a high recurrence rate at the original site. MFS of the head and neck is rare, while it occurs in the maxilla and mandible is extremely rare. Case presentation We report a case of MFS of the mandible in a 51-year-old female who presented with a painless gingival swelling and mobile, super-erupted right mandibular second and third molars. Panoramic x-ray and maxillofacial CT revealed an ill-defined radiolucent lesion surrounding the mandibular molars giving a teeth-floating-in-air appearance. Histopathological examination showed scattered spindle and stellate cells with mild atypia distributed in the myxoid stroma. Only a few mitotic figures were identified and no area of tissue necrosis was found. The characteristic thin-walled and curvilinear vasculature were prominent. Immunohistochemistry analysis revealed the tumor cells being positive for vimentin and vascular CD31. CK, S-100, P63, HHF-35 stains were negative. The labeling index of Ki-67 was about 30%. Based on the histopathological and immunohistochemical examinations, the diagnosis of a low-grade MFS was established. This patient underwent a radical segmental excision with a 2-cm margin, supraomohyoid neck dissection and immediate reconstruction of the mandibular continuity defect with a fibular osteocutaneous free flap. This patient has been followed for 20 months to date and has remained disease free. Conclusions This report describes a rare case of MFS of the mandible. Recognizing the histopathological features of MFS and applying the appropriate immunohistochemical examinations are crucial in establishing the correct diagnosis. Our case may provide diagnosis and treatment experiences of MFS occurs in the mandible.